(untitled) (Journal of BP Koirala Institute of Health Sciences, 2023)
A medical curriculum may have teaching learning modalities involving both large group and small groups. Fostering student Interaction, engagement and collaboration is relatively easier in small group. Many of the small group teaching strategies are also applied for effective collaboration and communication to a large group. However, student motivation is the key to student engagement and learning. This editorial explores some of the very simple strategies which allow students opportunities to prepare for their learning as well as to reflect upon their learning. The activities enlisted are simple methods like quiz, practice test, providing lecture slides and lecture videos and giving assignments to students. What is emphasized here is to carry out these activities in a nonthreatening manner without pressure of ‘grades’.The best way would do this is through an online platform hence the provision of learning management system in a teaching institute is emphasized. Using online medium for these activities has two advantages: (i) it will allow the students to carry out the given work in solitude and it will enable us teachers to give one to one feedback or feedback in the form of corrected response. (ii). There is also an advantage of students getting exposed to a blend of both physical teaching learning, during lectures and small group teaching and an opportunity for using online platforms for activities.